Neurological disease caused by Oropouche virus in northern Brazil: should it be included in the scope of clinical neurological diseases? - Chiang, Jannifer Oliveira (Springer, 2021)
We describe two neurological cases of Oropouche virus infection in northern Brazil, where the virus is endemic but neglected as a pathogen. This study reiterates the necessity of developing protocols for diagnosing infections and training medical personnel to recognize the pathogenicity of Oropouche virus in neurological infections